2013
DOI: 10.1016/j.ijmyco.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Performance of light-emitting diode fluorescence microscope for diagnosis of tuberculosis

Abstract: Although the use of LED-FM only marginally increased sensitivity, the considerable time saving ability combined with very good acceptance and ease of use makes it a reliable alternative to other conventional methods available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 8 publications
3
21
1
Order By: Relevance
“…Although sensitivity might not represent a major advantage over ZN microscopy, the device-associated reduction in laboratory workload [3,14,15,21,23] remains a strong advantage in terms of cost-efficiency. LED-FM specificity is overall high and should not be a barrier to device introduction in high-TB-burden and limited-resource countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although sensitivity might not represent a major advantage over ZN microscopy, the device-associated reduction in laboratory workload [3,14,15,21,23] remains a strong advantage in terms of cost-efficiency. LED-FM specificity is overall high and should not be a barrier to device introduction in high-TB-burden and limited-resource countries.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported provision of training of various length [13,14,16,[19][20][21]23], but training provision did not consistently translate into better LED-FM performance accuracy (data not shown). …”
Section: Subgroup Accuracy Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…These specimens were collected and packed with ice gel pack and transported through courier as per standard operating procedure from DTC's to the laboratory. The smear microscopy was performed by fluorescent microscopy method (Auromine-O)-light emitting diode FM [22]. Based on smear microscopy results, the smear positive specimens 4897 were subjected to LPA genotypic method.…”
Section: Specimens and The Study Populationmentioning
confidence: 99%